The Effects of Oral Contraceptives on the Risk of Ovarian Cancer - Payandeh, Rachelle (SFU Health Sciences Undergraduate Journal, 2023)
Numerous studies have assessed potential prevention methods to reduce the risk of gynaecological cancers. The current study investigates how oral contraceptive use can decrease a woman’s risk for ovarian cancer. The relationship between oral contraceptive use and ovarian cancer, the effects of dose and duration of use, and the potentially greatly beneficial effects for high-risk individuals are thoroughly explored. The reviewed literature provided strong support that oral contraceptive use decreases a woman’s risk for ovarian cancer. Thus, the thesis that oral contraceptives protect against ovarian cancer was supported.